The Beagle Brain in Stereotaxic Coordinates - Palazzi, Xavier; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Beagles are the preferred canine model for safety studies in preclinical research and neuroscience. The central nervous system is often a target for pharmaceuticals, medical devices and chemicals, and a deep knowledge of the gross and microscopic anatomy of the beagle brain is mandatory for anatomic pathologists and neuroscience researchers in order to assess the safety of innovative medicinal and industrial chemicals as well as to investigate new mechanisms of action. But as was pointed out at the 2008 European Society of Toxicologic Pathology Congress, there is a dearth of published data on the beagle brain: Thus the need for this timely atlas. The Beagle Brain in Stereotaxic Coordinates is an up-to-date atlas of the beagle brain. It provides stellar illustrations of the organization of nerve tracts and the morphology of the nuclei that compose the central nervous system, and it includes serial cross sections to help readers better imagine what the whole three-dimensional picture looks like. Aimed at neuroscientists, neuroanatomists, neuropathologists, neurosurgeons, and students, this comprehensive atlas also serves as a guide to understand the comparative brain structure of other mammals given the striking similarity of nuclei and tracts between beagles and other mammals.
Keywords: Medicine; Neurosciences; Human anatomy; Neurobiology; Biomedicine; Neurosciences; Neurobiology; Anatomy